Angiotensin-converting enzyme is a modifier of hypertensive end organ damage - Xiaojun Liu (2018)
Severe forms of hypertension are characterized by high blood pressure combined with end organ damage. Through the development and refinement of a transgenic rat model of malignant hypertension incorporating the mouse renin gene, we previously identified a quantitative trait locus on chromosome 10, which affects malignant hypertension severity and morbidity. We next generated an inducible malignant hypertensive model where the timing, severity, and duration of hypertension was placed under the control of the researcher, allowing development of and recovery from end organ damage to be investigated. We have now generated novel consomic Lewis and Fischer rat strains with inducible hypertension and additional strains that are reciprocally congenic for the refined chromosome 10 quantitative trait locus. We have captured a modifier of end organ damage within the congenic region and, using a range of bioinformatic, biochemical and molecular biological techniques, have identified angiotensin-converting enzyme as the modifier of hypertension-induced tissue microvascular injury. Reciprocal differences between angiotensin-converting enzyme and the anti-inflammatory tetrapeptide, N-acetyl-Ser-Asp-Lys-Pro in the kidney, a tissue susceptible to end organ damage, suggest a mechanism for the amelioration of hypertension-dependent damage. © 2009 by The American Society for Biochemistry and Molecular Biology, Inc.